Rumah Kedai Sri Limbongan, Lot 381 & 384, Jalan Nara, Pasir Puteh, Kelantan / [lukisan teknik] - Massrol Nizzam Md. Salleh; Nurul Hamiruddin Salleh; Sahrudin Omar; Syahriah Sahat; Zarina Zakaria (Skudai : Universiti Teknologi Malaysia, 1995)
Kajian Lukisan Terukur (Fakulti Alam Bina) - Universiti Teknologi Malaysia, 1996